Computer simulation of the fire-tube boiler hydrodynamics; European Physical Journal Web of Conferences (EPJ Web of Conferences); Vol. 82 : Thermophysical Basis of Energy Technologies - Khaustov S. A. Sergey Aleksandrovich; Zavorin A. S. Aleksandr Sergeevich; Buvakov K. V. Konstantin Vladimirovich; Sheikin V. A. (2015, 2015)
Title screen